MODERN LIBERAL THEORIES: AXIOLOGICAL AND COMMUNICATIVE ASPECT - Абисова, М. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The article is devoted to the analysis of liberal communicative-contract models of social justice.